THE CONCEPT OF CORRUPTION, THE FACTORS THAT CAUSE IT - Nargizakhon Rakhimjonova (Galaxy International Interdisciplinary Research Journal, 2023)
Emergence of the "compliance control" system and its first stages in the fight against corruption.The phenomenon of corruption in the era of globalization is recognized worldwide as a transnational phenomenon. To combat it, today's world is testing various models. "Compliance-control" system penetrates many directions and stages of today's politics. We can see that this system is widely used in the social and economic spheres and in the fight against corruption in order to increase the effectiveness of the activities of state bodies and create fair competition.Today, the concept and mechanisms of "compliance-control" are new for the legal system of Uzbekistan, and before understanding its essence and analyzing the working mechanisms, we would like to dwell on certain concepts and some aspects of corruption.